2018
DOI: 10.1139/cjss-2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil phosphorus balance and phosphorus-use efficiency under long-term fertilization conducted on agriculturally used Chernozem in Germany

Abstract: This study investigates changes in soil phosphorus (P) in different fertilization treatments applied since 1902 on Chernozem soil at a “Static Fertilization Experiment” in Germany. Total and plant-available soil P, and soil P balances were assessed at 0–30, 30–60, and 60–90 cm depth layers in unfertilized “Zero”, mineral “NK” and “NPK”, and combined mineral and organic “FYM + NK” (farmyard manure + NK) and “FYM + NPK” fertilization treatments. P-use efficiencies were determined for each crop in rotation (sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
6
11
0
Order By: Relevance
“…In an agricultural ecosystem, P fertilization is the most common practice for guaranteeing the crop yield [1,2]. A large amount of residual P was accumulated in cultivated soils after long-term P overfertilization [3,4,5], and it was converted into less soluble and more stable forms, resulting in a low P use efficiency (PUE) (10-50%) [6,7]. Excessive P fertilizers caused soil Olsen-P to rapidly increase and resulted in a risk of nonpoint source pollution [8,9], but the crop yields were not improved by much [10].…”
Section: Introductionmentioning
confidence: 99%
“…In an agricultural ecosystem, P fertilization is the most common practice for guaranteeing the crop yield [1,2]. A large amount of residual P was accumulated in cultivated soils after long-term P overfertilization [3,4,5], and it was converted into less soluble and more stable forms, resulting in a low P use efficiency (PUE) (10-50%) [6,7]. Excessive P fertilizers caused soil Olsen-P to rapidly increase and resulted in a risk of nonpoint source pollution [8,9], but the crop yields were not improved by much [10].…”
Section: Introductionmentioning
confidence: 99%
“…The interactive effects of organic fertilizer and mineral N fertilizer was significant for moderately labile or stable P stocks, which indicated that P desorption and mineralization could be increased when other nutrients such as N and C are applied in sufficient amounts. In turn, P associated with OM could be transferred to deeper soil layers, causing increased P content in subsoil ( Medinski et al., 2018). Several other processes potentially could be involved, such as: Input of labile OM could facilitate the mobilization of P from stable P pools to labile P pools in the upper subsoil where surface application of organic and mineral fertilizers did not replenish P taken up by the crops.…”
Section: Discussionmentioning
confidence: 99%
“…Soil P sorption capacity decreased by long‐term excessive P fertilization ( Koch et al., 2018). When topsoil P sorption capacity declines due to continuous P fertilizer input, increasing leaching of P into deeper soil layers may occur ( Medinski et al., 2018). In addition, it was reported that higher P stocks in upper subsoil due to P leaching occurred in agricultural ( Kang et al., 2011), grassland ( Toor et al., 2005), and forest ecosystems ( Frossard et al., 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2018) found that for the control, N and NK treatments, the Olsen-P concentrations declined by between 0.46 and 0.73 mg P•kg -1 soil•year -1 , whereas for the P-containing treatments the rates of increase ranged from 1.68 to 17.5 mg P•kg -1 soil•year -1 , depending on the P balance. According to Medinski et al (2018), crop cultivation without P fertilization in control and NK treatments resulted in negative P balances and reduction of available P below recommended levels. The observed phosphorus content in the plots without P addition (Check and NK) was slightly higher than the initial value of 15 mg•kg -1 soil.…”
Section: Content Of Available Nutrients In Soilmentioning
confidence: 99%